COMMENTS ON THE ARTICLE V.K. TATOCHENKO, A.V. GOLDSTEIN «THE MMR VACCINE AND AUTISM: SCIENTIFIC ILLITERACY AND IRRESPONSIBILITY OF MASS MEDIA THREATENS PUBLIC HEALTH» - V.K. Tatochenko (Педиатрическая фармакология)
.